Dual-Function Conductive Copper Hollow Fibers for Microfiltration and Anti-biofouling in Electrochemical Membrane Bioreactors - Liu, Defei; Chen, Xin; Bian, Bin; Lai, Zhiping; Situ, Yue (Frontiers in Chemistry, 2018)
Membrane bioreactors (MBRs) with polymeric/ceramic microfiltration (MF) membranes have been commonly used for wastewater treatment today. However, membrane biofouling often results in a dramatically-reduced service life of MF membranes, which limits the application of this technology. In this study, Cu hollow fiber membranes (Cu-HFMs) with low resistivity (104.8 - 309.8 nΩ·m) and anti-biofouling properties were successfully synthesized. Further analysis demonstrated that Cu-HFMs reduced at 625 oC achieved the bimodal pore size distribution of ~ 1 μm and a porosity of 46%, which enable high N2 permeance (1.56×10-5 mol/m2 s pa) and pure water flux (5812 LMH/bar). The Cu-HFMs were further applied as the conductive cathodes, as well as MF membranes, in the electrochemical membrane bioreactor (EMBR) system that was enriched with domestic wastewater at an applied voltage of 0.9 V. Excellent permeate quality (Total suspended solids (TSS) = 11 mg/L) was achieved at a flux of 9.47 LMH after Cu-HFM filtration, with relatively stable transmembrane pressure (TMP) and low Cu2+ dissolvability (< 25 µg/L). The anti-biofouling over time was demonstrated by SEM characterization of the rare biofilm formation on the Cu-HFM cathode surface. By using Cu-HFMs in EMBR systems, an effective strategy to control the membrane biofouling is developed in this study.